A Survey on the 5th Generation of Mobile Communications: Scope, Technologies and Challenges - Sousa, Marco (2018)
The 5th Generation (5G) of mobile communicationswill impact the costumers Quality of Experience (QoE) by ad-dressing the current mobile networks usage trends and providingthe technological foundation for new and emerging services.Additionally, 5G may provide a uniﬁed mobile communicationplatform, with multiple purposes, leveraging industries, servicesand economic sectors. In this paper, a 5G tutorial is presented,including the 5G drivers, main use cases, vertical markets anda current status of the standardization process. Furthermore,several 5G key enabling technologies are presented, concerningthe Radio Access Network (RAN) and Core Network (CN)perspectives. Finally, a brief outline over the Internet of Things(IoT) concept and current research topics is presented.